Tacky goes to camp - Lester, Helen (Houghton Mifflin Books for Children, 2009)
Tacky the penguin and his friends go to Camp Whoopihaha where they scare each other by telling ghost stories around the campfire, never expecting that one of the frightening stories will come true.